A waste-derived nanocomposite sealant for repairing micro-cracks in concrete. (1st May 2022) - Kannan, Uthradevi; Gafoor, Shibil Abdul; Srivastava, Sonali; Nithyadharan, M.; Gupta, Soujit Sen; Maliyekkal, Shihabudheen M.
Abstract: The use of renewable resources has been gaining interest due to their high economic benefits. They are attractive as a sustainable alternative to conventional resources for producing useful and valuable materials. The paper focuses on using a composite of graphene-oxide and chitosan, an aquaculture waste-derived material, as a renewable feedstock for producing a sealant for healing micro-cracks in concrete. The sealant named Eco-Nanoseal is well characterised, and its interaction with concrete is studied. A possible binding mechanism of Eco-Nanoseal with concrete is proposed. The nanofibrous film-forming composite can quickly solidify in the concrete environment without any external polymerising agent. The quick ability to form a solid plug and strong bonding with the concrete surface makes Eco-Nano seal a potential candidate for healing micro-cracks in concrete. The novel application is demonstrated well in M25 grade concrete cube specimens. With low environmental factor (E-factor) and process mass intensity (PMI) values of 0.05 and nearly 1, respectively, the Eco-Nanoseal complies the critical parameters of materials' sustainability indices. The Eco-Nanoseal is a promising and environmentally-friendly alternative to synthetic polymer-based adhesives. Graphical abstract: Image 1 Highlights: A novel application of aquatic waste derived material as a micro-crack sealant An eco-friendly nanocomposite for sealing micro-cracks in concrete A sustainable method for recycling chitosan-based waste materials A hydraulically stable adhesive with ductile characteristics Mechanism of interaction of chitosan with hydrated cement is proposed